Strategi Peningkatan Penjualan dan Pengelolaan Kas Kecil di Apotek Stepa Imogiri - Ismiatun, Haniffah; Dewi Astuti , Tutut (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
With the right and creative strategy, pharmacy sales can increase. Two important elements are discussed: methods to increase sales and petty cash management. Pharmacies can increase sales in various ways by utilizing digital technology, offering discounts, and loyalty programs to encourage repeat purchases. Efficient petty cash management can facilitate cash flow management. Through staff training on petty cash management, its optimal use can be ensured. With the integration of sales enhancement strategies and effective petty cash management, profitability can be increased and good service can be provided to customers, thereby enabling competitiveness.